2003
DOI: 10.1248/bpb.26.544
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Attenuates Oxygen-Glucose Deprivation- and Excitotoxin-Induced Neurotoxicity in Primary Cortical Cell Cultures.

Abstract: The possible role of quercetin, a naturally occurring plant flavonoid, in protecting against oxygen-glucose deprivation (OGD)-, excitotoxins-, and free radical-induced neuronal injury in mouse cortical cell cultures was investigated. Pre- and co-treatment with quercetin (100 microM) inhibited 50 min OGD-, 20 microM N-methyl-D-aspartate (NMDA)-, and 50 microM kainate-induced neurotoxicity by 36, 22, and 61%, respectively. Quercetin significantly ameliorated free radical-induced neuronal injury caused by buthion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 18 publications
2
17
2
Order By: Relevance
“…(n = 7 per group). ficus-indica, had a neuroprotective action against NMDA-, KA-, and OGD-induced neurotoxicity in the same culture system (Ha et al, 2003). The results of the present study indicate that the Opuntia ficus-indica extract had a neuroprotective effect against NMDA-, KA-, and OGD-induced neurotoxicity in cultured cortical cells, which is consistent with the in vivo global ischemia scores.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(n = 7 per group). ficus-indica, had a neuroprotective action against NMDA-, KA-, and OGD-induced neurotoxicity in the same culture system (Ha et al, 2003). The results of the present study indicate that the Opuntia ficus-indica extract had a neuroprotective effect against NMDA-, KA-, and OGD-induced neurotoxicity in cultured cortical cells, which is consistent with the in vivo global ischemia scores.…”
Section: Discussionsupporting
confidence: 88%
“…Components isochondria, activate the release of cytochrome C or enzymes (proteases and phospholipases) that initiate cascades culminating in cell death during ischemic neuronal injury (Siesjo, 1988;Kobayashi et al, 2003). Experimental studies of the efficacy of Opuntia ficus-indica or one of its components, quercetin, against neuronal injury owing to free radicals, oxygen-glucose deprivation (OGD), or excitotoxin in mouse cortical cell cultures were reported recently (Wie, 2000;Ha et al, 2003). Specifically, the methanol extract of Opuntia ficus-indica (MEOF) produced dose-dependent neuroprotective effects on hydroxyl-and superoxide radical-mediated neuronal damage to primary cortical cultures.…”
Section: Introductionmentioning
confidence: 99%
“…We did not encounter with any published data about combined treatment of quercetin with menadione on cultured glial cells. Ha et al (2003) reported that both pre-and co-treatment with 1-10 lM concentrations of quercetin did not have a neuroprotective effect; however concentrations of quercetin of 30-100 lM protected against neurotoxicity induced by different excitotoxins in mouse primary cortical cultures for 20 and 24 h. We have found in another study that 100 lM H 2 O 2 alone decreased the glial cell number Fig. 4 The pre-treatment and co-treatment effects of quercetin concentrations on 75 lM menadione toxicity for 6 h on glial cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment of quercetin protects against hydrogen peroxide (Saito et al 2004), glucose oxidase ) and menadione (Aherne and O'Brien 2000;Park et al 2003) induced toxicity in different cell types. It was reported that both pre-and co-treatment of quercetin with different exitotoxins showed a neuroprotective activity on mouse primary cortical culture (Ha et al 2003). Although the multiple activities of quercetin were believed to be due to its strong antioxidant properties (Lee et al 2001), recent studies indicated that it has prooxidant and cytotoxic effects on different cell types (Matsuo et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, quercetin (3,3',4',5,7-pentahydroxyflavone), another flavone, was reported to protect against apoptotic cell death via an increase in the expression of antiapoptotic Bcl-2 family proteins (37). Since quercetin is similar to wogonin in relation to pharmacological properties such as being an antioxidant (37) and exerting anti-inflammatory (35,38) and neuroprotective (39,40) effects, the inhibition of apoptosis by wogonin may be involved with regulating the expression of Bcl-2 family members. A study of the inhibition mechanism of glucocorticoid-induced apoptotic cell death is in progress in our laboratory.…”
Section: Discussionmentioning
confidence: 99%